Genomic analysis of dibenzofuran-degrading Pseudomonas veronii strain Pvy reveals its biodegradative versatility. Issue 2 (9th December 2020) - Lopez-Echartea, Eglantina; Suman, Jachym; Smrhova, Tereza; Ridl, Jakub; Pajer, Petr; Strejcek, Michal; Uhlik, Ondrej
Abstract: Certain industrial chemicals accumulate in the environment due to their recalcitrant properties. Bioremediation uses the capability of some environmental bacteria to break down these chemicals and attenuate the pollution. One such bacterial strain, designated Pvy, was isolated from sediment samples from a lagoon in Romania located near an oil refinery due to its capacity to degrade dibenzofuran (DF). The genome sequence of the Pvy strain was obtained using an Oxford Nanopore MiniION platform. According to the consensus 16S rRNA gene sequence that was compiled from six 16S rRNA gene copies contained in the genome and orthologous average nucleotide identity (OrthoANI) calculation, the Pvy strain was identified as Pseudomonas veronii, which confirmed the identification obtained with the aid of MALDI-TOF mass spectrometry and MALDI BioTyper. The genome was analyzed with respect to enzymes responsible for the overall biodegradative versatility of the strain. The Pvy strain was able to derive carbon from naphthalene (NP) and several aromatic compounds of natural origin, including salicylic, protocatechuic, p -hydroxybenzoic, trans -cinnamic, vanillic, and indoleacetic acids or vanillin, and was shown to degrade but not utilize DF. In total seven loci were found in the Pvy genome, which enables the strain to participate in the degradation of these aromatic compounds. Our experimental data also indicate that the transcription of the NP-dioxygenase α-subunit gene ( ndoB ), carried by the plasmid of the Pvy strain, is inducible by DF. These features make the Pvy strain a potential candidate for various bioremediation applications.